2014
DOI: 10.1186/1471-2164-15-303
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoxia exerts parallel and cell-specific regulation of gene expression and alternative splicing in human mesenchymal stem cells

Abstract: BackgroundThe endosteum of the bone marrow provides a specialized hypoxic niche that may serve to preserve the integrity, pluripotency, longevity and stemness of resident mesenchymal stem cells (MSCs). To explore the molecular genetic consequences of such a niche we subjected human (h) MSCs to a pO2 of 4 mmHg and analyzed global gene expression and alternative splicing (AS) by genome-exon microarray and RT-qPCR, and phenotype by western blot and immunostaining.ResultsOut of 446 genes differentially regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 76 publications
4
47
0
Order By: Relevance
“…As one approach to investigate mechanism of HPC, we compared global gene expression profiles of normoxic versus hypoxia preconditioned hMSCs by microarray and found that leptin was the most strongly hypoxia‐induced gene . This is in agreement with another study that found leptin to be similarly induced by hypoxia in adipose tissue‐derived stem cells as well as with the known presence of active hypoxia‐induced factor 1α (HIF‐1α) binding elements in the leptin gene promoter .…”
Section: Introductionsupporting
confidence: 85%
“…As one approach to investigate mechanism of HPC, we compared global gene expression profiles of normoxic versus hypoxia preconditioned hMSCs by microarray and found that leptin was the most strongly hypoxia‐induced gene . This is in agreement with another study that found leptin to be similarly induced by hypoxia in adipose tissue‐derived stem cells as well as with the known presence of active hypoxia‐induced factor 1α (HIF‐1α) binding elements in the leptin gene promoter .…”
Section: Introductionsupporting
confidence: 85%
“…Comparative transcriptome analysis has been employed to investigate the cell response, particularly MSCs, in such 3D culture systems (Gatta et al, 2013;Hu et al, 2014;Kim et al, 2014;Pedersen et al, 2013;Roobrouck et al, 2011;Wu et al, 2012;Han et al, 2013; A C C E P T E D M A N U S C R I P T Jakobsen et al, 2014;Neuss et al, 2011). For example, a study by Han et on the scaffolds made with poly(lactic acid) than those made with poly(ɛ-caprolactone) (Neuss et al, 2011).…”
Section: Optimizing Culture Conditionsmentioning
confidence: 98%
“…The endosteum also contains pre-osteoblastic cadherin-2-expressing cells, and has nerve and blood supplies, 49 although tese features are difficult to detect with plain-light microscopy. The heterogeneous environment of the endosteum contains scattered sites of microvascular infiltration associated with other regions of significant hypoxia, 50 which are highly attractive regions for HSC-homing. 5153 Interestingly, quiescent HSCs tend to reside in areas of very low blood perfusion, whereas more proliferative HSCs with a lower reconstitution potential tend to prefer areas with greater blood flow.…”
Section: Biochemistry Of the Nichementioning
confidence: 99%